Novel Therapeutic Targets in Heart Failure: The Phospholipase Cβ1b-Shank3 Interface - Woodcock, Elizabeth A.; Grubb, David R. (Clinical medicine insights. Therapeutics, 2015)
Inotropic agents are often used to improve the contractile performance of the failing myocardium, but this is often at a cost of increased myocardial ischemia and arrhythmia. Myocyte contractility depends on the release of Ca2+ from the sarcoplasmic reticulum, and this Ca2+ is subject to regulation by the phosphorylation status of phospholamban (PLN). Many currently used inotropic agents function by increasing the phosphorylation of PLN, but these also heighten the risk of ischemia. Another approach is to reduce the dephosphorylation of PLN, which can be achieved by inhibiting pathways upstream or downstream of the protein kinase Cα. Phospholipase Cβ1b is responsible for activating protein kinase Cα, and its activity is substantially heightened in failing myocardium. We propose phospholipase Cβ1b, a cardiac-specific enzyme, as a promising target for the development of a new class of inotropic agents. By reversing changes that accompany the transition to heart failure, it may be possible to provide well-tolerated improvement in pump performance.